Desempenho agronômico de populações de milho-pipoca sob o uso de inoculantes em cultivo orgânico e variedades tradicionais de milho em diferentes níveis de fósforo - Guirado, Gabriel Cipolaro (2016)
The objectives of this work are: a) to evaluate the growth, development and yield performance of popcorn populations in response to inoculation with bacteria that promote growth and identify promising populations for organic farming; b) assess traditional maize populations under different phosphorus levels and identify efficiencies and answers to this element. The work was divided into two experiments, namely: a) the first was to evaluate the agronomic performance of popcorn populations with the use of inoculants. They evaluated the popcorn production of components, most relevant being to culture the yield and scalability. The experimental design was a randomized complete block in a split plot, where inoculants were allocated the plots and popcorn populations in the subplots, with three replications and the means of variables were submitted to the Scott-Knott test a 5% probability. In the second experiment eighteen varieties of maize underwent two environments with different levels of phosphorus and then were assessed for production of components, as well as phosphorus in grains, phosphorus utilization coefficient, harvest index, purchasing efficiency, useful efficiency and phosphorus use efficiency, in addition to an analysis by the method proposed by Fageria and Kluthcouski (1980). In the first study, the results indicated that there was no interaction between the inoculant and the populations of popcorn. Within populations, with significant results for mass of one hundred grains, grain yield and CE stand out Aelton and Gaucho. In the second study the results show that the ST 0509 population showed high performance in grain yield in both environments and high efficiency and low phosphorus reply. The most efficient and responsive population using P is the Amarelão.